RECURRENT PREGNANCY LOSS - Nofa Cholili, Muhamad; Wiyasa, Arsana (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Miscarriage occurs when the fetus is unable to survive outside the womb and the results of conception are expelled. Although the issue of RPL is still controversial, current information about the suggested treatment offers effective treatment to improve reproductive quality and can provide appropriate therapy in a woman with RPL based on the etiology. The time restriction until the fetus is pronounced viable or capable of surviving outside the womb varies by country. According to the World Health Organization, over 21.6 million abortions occurred worldwide in 2008, with almost all of these cases occur in developing countries. The risk of miscarriage increases most significantly at the age of 35 years. Women aged 35 years have twice the risk of miscarriage compared to women aged < 35 years. Antiphospholipid syndrome is a risk factor for recurrent miscarriage, which occurs in about 15% of patients. The reason of recurrent miscarriage can be linked to both fetal and maternal factors. Diagnostic examinations are not recommended in patients with recurrent miscarriage unless certain criteria are met. However, screening can be used to identify risk factors. The management of recurrent miscarriage should be addressed toward the underlying cause with a treatable etiology or pathophysiology.